Prototyping / The Effective Use of CASE Technology - Vonk Roland (Prentice Hall, 1990)
This book aims to clarify the prototyping concept by discussing all the major facets of this approach to requirements definition. Preface, The Prototyping Concept, Meeting the Organization's Information Needs, Prototyping - Concepts and Terminology, Introduction and Use of Prototyping, A Detailed View of the Prototyping Process, Initiation Phase, The Further Course of the Project, The Technology Behind Prototyping, Basic Concepts of Data Dictionary Systems, Analyst Workbenches, Fourth-Generation Languages, The State of the Art, The ISO Three-level Approach, Index.